2019
DOI: 10.15761/rri.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine cardiomyopathy: A review and pooled analysis of pathophysiology, diagnosis and clinical management

Abstract: Evidence associating endocrinopathies such as diabetes, thyroid and growth hormone disorders with cardiomyopathies (CMs) and heart failure (HF) has been longestablished. Initially, endocrine disorders were considered an independent risk factor for the development of HF. However, increasing diagnosis of endocrine disorders in patients with CM suggest the involvement of hormones in the pathogenesis of CMs. Moreover, the success of hormonal replacement therapies in a sub-population of patients diagnosed with dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 136 publications
(288 reference statements)
0
4
0
Order By: Relevance
“…Supplementation with thyroid and adrenal hormones improved QT prolongation and tent-like Twaves on the ECG, and TdT did not recur. Albakri et al reported a case of cardiogenic shock due to self-interruption of hormone replacement after pituitary adenoma removal (15). They described the role of the pituitary gland in maintaining proper cardiovascular status.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with thyroid and adrenal hormones improved QT prolongation and tent-like Twaves on the ECG, and TdT did not recur. Albakri et al reported a case of cardiogenic shock due to self-interruption of hormone replacement after pituitary adenoma removal (15). They described the role of the pituitary gland in maintaining proper cardiovascular status.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endocrine dysfunction and certain metabolic syndromes have been linked with the disease (12,13). Dilated cardiomyopathy can occur secondarily to neuromuscular causes (14).…”
Section: Introductionmentioning
confidence: 99%
“…Of significance, certain chemotherapeutic agents have important side effects that progress towards a DCM phenotype either acutely or years after administration (8–11). In addition, endocrine dysfunction and certain metabolic syndromes have been linked with the disease (12,13). Dilated cardiomyopathy can occur secondarily to neuromuscular causes (14).…”
Section: Introductionmentioning
confidence: 99%
“…Prior reviews have dealt with pathophysiology and cardiac manifestations of various endocrine disorders. 2 , 3 Here, we shall discuss endocrine disorders with potential of index presentation with HF. Except for thyroid disorders, pheochromocytoma/paraganglioma (PPGL) and primary hyperaldosteronism, other disorders dealt in this review have rare presentations.…”
Section: Introductionmentioning
confidence: 99%